THE FORMATION OF THE CONCEPT OF TEMPORALITY IN THE LINGUISTIC LANDSCAPE OF THE WORLD - Kurbonova Surayyo Anvarovna (Bright Mind Publishing, 2025)
This article explores the formation and representation of the concept of temporality across diverse linguistic and cultural landscapes. By analysing linguistic structures, metaphors, and time-related expressions in different languages, the study reveals how temporality is not only a universal cognitive category but also a culturally constructed phenomenon. It shows that while all human languages express temporal relations, they do so in distinct ways that reflect underlying cultural models of time.
Keywords: Conceptualisation, communication, temporal relations, tense, aspect, adverbials, temporal metaphors.